2011
DOI: 10.1159/000321000
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Screening of Children for Specific Speech and Language Impairment in Germany: A Systematic Review

Abstract: Objective: The study was aimed at evaluating the effectiveness of a systematic population-based screening programme for specific language impairment (SLI) in preschool children in Germany. Methods: The study question was divided into a review of (1) evidence from studies evaluating screening programmes, (2) diagnostic instruments in the German language, and (3) studies evaluating speech and language interventions. A systematic database search was conducted between June and October 2007 and was updated in Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 138 publications
1
20
0
1
Order By: Relevance
“…In this study 26 tests differentiated children with SLI from matched control children at the group level. Furthermore, the language deficits of children with SLI in Finnish that were found in this study are consistent with those found in international studies [7,8,16,17]. On a local basis, the result increases the clinicians' confidence, both physicians' and SLTs', in language tests even in the case of smaller populations with their own languages, such as Finnish.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study 26 tests differentiated children with SLI from matched control children at the group level. Furthermore, the language deficits of children with SLI in Finnish that were found in this study are consistent with those found in international studies [7,8,16,17]. On a local basis, the result increases the clinicians' confidence, both physicians' and SLTs', in language tests even in the case of smaller populations with their own languages, such as Finnish.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the performance of different available tests has not been compared in populations of children with SLI. Thus, we have limited knowledge about these tests in Finland as well as in other countries [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Specific speech and language impairments affect up to around 7% at school entry17 18 This is a developmental language disorder that affects the development of an individual's spoken or receptive language despite their having adequate intelligence, accessibility to learning and no comorbid neurological deficit. Language skills are strongly associated with literacy levels and both are predictive of educational attainment after controlling for IQ and maternal education 19.…”
Section: Specific Speech and Language Impairmentsmentioning
confidence: 99%
“…Regarding the prevalence of SLI, data are rare and vary widely (10). A number of studies have been conducted in order to determine the prevalence of SLI in different populations.…”
Section: Introductionmentioning
confidence: 99%